A Study on “Attitude and Acceptance of Fortified Foods in Urban Areas” - Shivani Singh, Divya Chandel, (Indian Journal of Extension Education, 2018)
Food fortification is the addition of one or more essential nutrients to a food whether or not it is normally contained in thefood, for the purpose of preventing or correcting a demonstrated deficiency of one or more nutrients in the population orspecific population groups. Food fortification is the practice of deliberately increasing content of an essential micronutrient in a food, so as to improvise the nutritional quality of the food supply and provide a public health benefit withminimal risk to health. The fortified market today largely consists of health food drinks, iodized salt, iron fortified biscuitsand fortified edible oils. Health food drinks have been focused on general nutritional needs of growing children whileiodized salt and iron- fortified biscuits have become mass product segments driven by nutrient deficiencies and supportthrough various government policies. Some of the major companies operating in the global market for vitamin fortifiedand mineral enriched foods and beverages include The Pepsico Company, Mother Dairy, Quaker, Kellogg Company andThe Proctor & Gamble Company and so on. The present study entitled “Attitude and acceptance of fortified foods in urbanareas, a study – is a case study of Delhi/National Capital Region (NCR) metro consumers” that scatters light on the buyer'spreferences towards fortified foods.